Pengembangan Multimedia Pembelajaran Interaktif Menggunakan Aplikasi Articulate Storyline - Muhammad Syahrul; Fetri Yeni J (Journal of Pedagogy and Online Learning, 2023)
The purpose of this study id to find out how to develop interactive learning multimedia using the articulate storyline application, to find out the validity and practicality of interactive learning multimedia in class VIII at indonesian subject at MTsN 6 Padang. The results of the material validity test are in the "Very Valid" category with a percentage of 88,42%, the media validation results are in the "Very Valid" category with a percentage of 95% so that flipbook-based learning media products can be tested. Furthermore, the results of the product practicality test are in the "Very Practical" category with a percentage of 87%, so that interactive learning media products are suitable for use by VIII grade islamic high school students as learning media.